The flood pulse regulates the longitudinal distribution of fish assemblages in the amazonian floodplain lakes - Raniere Garcez Costa Sousa; Nathalya Sousa Oliveira; Fábio Ricardo da Rosa (Boletim do Instituto de Pesca)
The present study evaluated the incidence of fish species in Cujubim Lake in Porto Velho (Rondônia, Brazil) concerning periods of flood and low water. For this, we used experimental fisheries, with ichthyofauna samplings carried out in the years 2019 and 2020, which resulted in 2,508 specimens. For quantifying the ecological data, we analyzed Shannon-Weaver diversity, species richness, Simpson dominance and Pielou evenness. The predominant fish orders were Characiformes and Siluriformes, and the species Anchovia aff. surinamensis was the most abundant (N=809/35.49%). Diversity indicators were similar across all sectors (S1=the lower margin - end, S2=center and S3=mouth of the lake). Only the levels of richness and abundance were lower in the S3 sector, despite the importance of this habitat as a link to the Madeira River, which indicates transient diversity, followed by active selection of the S1 and S2 sectors in the lake by most fish. Limnological data, such as those of temperature (30.30±1.20°C), conductivity (35.82±5.98 µS cm-1), dissolved oxygen (7.38±3.56 mg L-1) and pH (6.70±0.54), were within the acceptable levels for tropical fish. The non-metric multidimensional scaling (NMDS) analysis showed the ordering of parameters by sector and species with greater affinity for each environmental attribute, in which dissolved oxygen (NMDS1=-0.720; r2=0.862 and p=0.043) and electrical conductivity stood out. Thus, it can be concluded that the behavior of the fish diversity of Cujubim Lake is affected both seasonally and longitudinally.